Phase Morphology of Multiblock Copolymers Differing in Sequence of Blocks. Issue 3 (2nd February 2021) - Behl, Marc; Balk, Maria; Mansfeld, Ulrich; Lendlein, Andreas
Abstract: The chemical nature, the number length of integrated building blocks, as well as their sequence structure impact the phase morphology of multiblock copolymers (MBC) consisting of two non‐miscible block types. It is hypothesized that a strictly alternating sequence should impact phase segregation. A library of well‐defined MBC obtained by coupling oligo(ε‐caprolactone) (OCL) of different molecular weights (2, 4, and 8 kDa) with oligotetrahydrofuran (OTHF, 2.9 kDa) via Steglich esterification results in strictly alternating (MBCalt ) or random (MBCran ) MBC. The three different series has a weight average molecular weight ( M w ) of 65 000, 165 000, and 168 000 g mol −1 for MBCalt and 80 500, 100 000, and 147 600 g mol −1 for MBCran . When the chain length of OCL building blocks is increased, the tendency for phase segregation is facilitated, which is attributed to the decrease in chain mobility within the MBC. Furthermore, it is found that the phase segregation disturbs the crystallization by causing heterogeneities in the semi‐crystalline alignment, which is attributed to an increase of the disorder of the OCL semi‐crystalline alignment. Abstract : The phase morphology of a library of well‐defined multiblock copolymers (MBC) composed of two different hydrophobic, semi‐crystalline blocks synthesized as strictly alternating (MBCalt ) or random (MBCran ) MBC providing domains with well‐separated melting temperatures ( T m s) is analyzed and the influence of molecular weight and length of the precursor building blocks is discussed.